(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
The article scientifically examined the causes and specific aspects of Amir Temur’s military campaigns, as well as measures to expand the national territory. The article, based on the opinions and views of scientists who conducted research on this topic, highlighted the specific aspects of Amir Temur’s military campaigns and measures to expand the national territory.